ADVANTAGES OF NEW INFORMATION TECHNOLOGY IN ENGLISH LANGUAGE TEACHING IN HIGH SCHOOLS - Khusanova, Indira (Журнал иностранных языков и лингвистики, 2023)
In our article, experimental classes will be conducted by teachers of many higher education institutions with examples from departments and basic preparatory educational institutions in remote places, and an evaluation of similar classes will be considered. Currently, high school teachers use telecommunications mainly as a complement to existing courses and subjects in extracurricular activities to separate experiences with students.